In vitro inhibition studies of coumarin derivatives on Bos taurus enolase and elucidating their interaction by molecular docking, molecular dynamics simulations and MMGB(PB)SA binding energy calculation - DANIŞ, ÖZKAN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Tropical theileriosis is among the most common vector-borne diseases and caused by Theileria parasites. Theileria annulata is an obligate intracellular protozoan parasite and transmitted to especially Bos taurus and Bos indicus by Hyalomma tick vectors. C8 ([4-(3,4-dimethoxyphenyl)-6,7-dihydroxy-2H-chromen-2-one); C9 (4-(3,4-dihydroxyphenyl)-7,8 dihydroxy-2H-chromen-2-one); C21 (4-(3,4-dihydroxyphenyl)-6,7-dihydroxy-2H-chromen-2 one) were identified as potent Theileria annulata enolase (TaEno) inhibitors in our previous studies. An ideal drug compound must inhibit the target parasite enzyme without inhibiting its homolog in the host. In this study, the inhibitory effect of the compounds previously evaluated on TaEno were tested on the host Bos taurus enolase (BtEno3) by in vitro studies. The interactions of enzyme-coumarin and enzyme-coumarin-substrate by in silico studies were also performed. All of the coumarin derivatives tested showed very low inhibitory effects on B. taurus enolase; 36,87% inhibition at 100 mu M concentration for C8, 8,13% inhibition at 100 mu M concentration for C9 and 77,69 mu M of IC50 value for C21. In addition, these three coumarin derivatives and substrate 2PG were docked into the BtEno3 using molecular docking methods. Molecular interactions between enolase-coumarin and enolase-coumarin-substrate complexes were analyzed using molecular dynamics simulation methods for 100 ns. Estimated free energy of bindings of the substrate 2PG and coumarin derivatives to the BtEno3 were calculated by MM-GB(PB)SA methods. In comparison to the inhibition studies performed on TaEno, C8 and C9 coumarin derivatives remain the possible inhibitor candidates as they inhibit the host enolase at very high concentrations. These two promising compounds will be further analyzed by in vitro and in vivo studies towards developing an alternative drug against tropical theileriosis.
Keywords: Bos taurus enolase; Theileriosis; Structure-based drug design; Molecular dynamics simulations; THEILERIA-ANNULATA; CRYSTAL-STRUCTURE; COMPLEX; GENE; ALGORITHM; MECHANISM; RECEPTOR; CLONING; DESIGN; ENZYME